Scriptural authority in early Judaism and ancient Christianity - Kalimi, Isaac; Nicklas, Tobias; Xeravits, Géza G.; Hötzinger, Heike (Deuterocanonical and cognate literature studies, 2013)
The impact of earlier works to the literature of early Judaism is an intensively researched topic in contemporary scholarship. This volume is based on an international conference held at the Sapientia College of Theology in Budapest, May 18-21, 2010. The contributors explore scriptural authority in early Jewish literature and the writings of nascent Christianity. They study the impact of earlier literature in the formulation of theological concepts and books of the Second Temple Period.